Confronting chronic career stress. - SHUFORD, JOHN A. (Corrections Today)
The article focuses on addressing chronic career stress in the criminal justice system, emphasizing the importance of implementing immersive experiential training to improve staff wellbeing and reduce negative health outcomes. Topics discussed include the detrimental effects of isolation on staff, the significance of emotional intelligence in workplace culture, and the positive impact of experiential training on staff attitudes and behaviors.